ANALISIS NILAI MORAL NOVEL ANAK SEJUTA BINTANG KARYA AKMAL NASERY BASRAL - Maguna Eliastuti (Pujangga: Jurnal Bahasa dan Sastra, 2016)
ABSTRACTThe purpose of this study was to determine and describe the content of the analysis of empirical dataabout the moral value of the novel Anak Sejuta Bintang. The method used in this research is qualitativemethod with a moral approach, focusing the study of structural analysis in the study of literature thatfocuses on the content of moral analysis contained in the novel "Children of a Million Stars" by AkmalNasery Basral. These results indicate that the presence of other aspects of good morality. Good moraltendency to researchers encountered in the novel Anak Sejuta Bintang by Akmal Nasery Basral of theoverall findings of valueKeywords : novel, Aanak Sejuta Bintang